Leadership to sustain innovation processes in school - López Yáñez, Julián; Lavié Martínez, José Manuel (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
We exam in this paper the findings of an inquiry on the institutional basis that let to develop sustainable change processes in schools from the perspective of leadership. In particular, we observed that some schools that presented a sustained dynamics of changes, deployed patterns of widely distributed leadership as well. In the paper, two cases in which such institutional dynamics were identified will be analyzed and confronted with a third case that failed in the attempt to carry out an important change project. In this case leadership adopted a clearly focalized pattern. The details of such processes are analyzed and discussed taking into account the literature about distributed leadership